Prospective pilot study protocol evaluating the safety and feasibility of robot-assisted nipple-sparing mastectomy (RNSM). Issue 11 (15th November 2021) - Park, Ko Un; Lee, Sandy; Sarna, Angela; Chetta, Matthew; Schulz, Steven; Agnese, Doreen; Grignol, Valerie; Carson, William E; Skoracki, Roman J
Abstract : Introduction: Nipple-sparing mastectomy (NSM) can be performed for the treatment of breast cancer and risk reduction, but total mammary glandular excision in NSM can be technically challenging. Minimally invasive robot-assisted NSM (RNSM) has the potential to improve the ergonomic challenges of open NSM. Recent studies in RNSM demonstrate the feasibility and safety of the procedure, but this technique is still novel in the USA. Methods and analysis: This is a single-arm prospective pilot study to determine the safety, efficacy and potential risks of RNSM. Up to 12 RNSM will be performed to assess the safety and feasibility of the procedure. Routine follow-up visits and study assessments will occur at 14 days, 30 days, 6 weeks, 6 months and 12 months. The primary outcome is to assess the feasibility of removing the breast gland en bloc using the RNSM technique. To assess safety, postoperative complication information will be collected. Secondary outcomes include defining benefits and challenges of RNSM for both surgeons and patients using surveys, as well as defining the breast and nipple-areolar complex sensation recovery following RNSM. Mainly, descriptive analysis will be used to report the findings. Ethics and dissemination: The RNSM protocol was reviewed and approved by the US Food and Drug Administration using the Investigational Device Exemption mechanism (reference number G200096). In addition, the protocol was registered with ClinicalTrials.gov (NCT04537312 ) and approved by The Ohio State University Institutional Review Board, reference number 2020C0094 (18 August 2020). The results of this study will be distributed through peer-reviewed journals and presented at surgical conferences. Trial registration number: NCT04537312 .